The objective of this Study is to identify the Effect of A program Based on the Mc Carthy Model (4 MAT) for the Development of Mental Motivation among the Student of 2nd Level, secondary School - Al-Kokabani, Ahmed Saleh Abdulla; Alem, Twfik Ali (Journal of Educational and Psychological Sciences, 2023)
The objective of this study is to identify the effect of a program based on the McCarthy model (4 MAT) for the 2nd level, secondary school. In order to achieve the goal of the study, the study subjects were divided into experimental and control groups, and the criteria were applied before and after the application of the program to the experimental group. The results of the study showed that there were statistically significant differences in the effectiveness of the program based on the form of 4 MAT in the development of mental motivation in the study sample at the level of (0.01) attributed to the program and for the benefit of the experimental group. The study recommended further studies based on the (4 MAT) Model for application Ar basic, intermediate, High Schools as well universities.